2022
DOI: 10.1073/pnas.2116775119
|View full text |Cite
|
Sign up to set email alerts
|

A nitroaromatic cathode with an ultrahigh energy density based on six-electron reaction per nitro group for lithium batteries

Abstract: Organic electrode materials have emerged as promising alternatives to conventional inorganic materials because of their structural diversity and environmental friendliness feature. However, their low energy densities, limited by the single-electron reaction per active group, have plagued the practical applications. Here, we report a nitroaromatic cathode that performs a six-electron reaction per nitro group, drastically improving the specific capacity and energy density compared with the organic electrodes bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…Profiting from strong electronegativity, nitro groups deliver powerful coupling capability and susceptibility to form metal–ligand complexes with electrolyte ions, affording robust redox nature [12] . Meanwhile, with the ability to accept two electrons per nitro group, it can trigger multielectron redox for efficient charge storage [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Profiting from strong electronegativity, nitro groups deliver powerful coupling capability and susceptibility to form metal–ligand complexes with electrolyte ions, affording robust redox nature [12] . Meanwhile, with the ability to accept two electrons per nitro group, it can trigger multielectron redox for efficient charge storage [13] .…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the chemical structures of cathode materials as well as electrolytes have a great influence on the performance of a battery. Thus, in this research, besides new cathode materials, we also used a more complicated electrolyte for this new nitro compound compared to the reported electrolytes for other nitro compounds. , Additionally, different values of CVs and different scanning rates were also optimized in order to obtain the voltage platform. Furthermore, at 1 A g –1 , the capacity could be maintained at 180 mAh g –1 after 1100 cycles (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Even so, this result clearly suggests that attaching nitro groups onto aromatic rings is an efficient method to improve the capacity of LIBs. More recently, Xu et al 43 reported that a nitroaromatic small molecule (1,5-dinitronaphthalene, 1,5-DNN) as a cathode compound in lithium primary batteries could give an ultrahigh specific capacity of 1338 mAh g −1 and an energy density of 3273 Wh kg −1 , which surpass those of all existing organic cathodes. They also found that a nitro group could perform a six-electron reaction, significantly increasing the specific capacity and energy density compared with other organic cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…in organic electrode materials can only experience singleelectron reaction per active group while the Zn 2+ ions carry two positive charges. 88 Thus, the coordination reaction between Zn 2+ and the organic electrode materials take place in adjacent electrochemical active groups within one molecule 58,[69][70][71]75 or from adjacent molecules. 67,68,78 In either case, the utilization rate of active groups is limited due to the restrictions on their spatial location.…”
Section: The Impact Of Proton Storage On Capacitymentioning
confidence: 99%